How addressing divisions on African migration inside the EU can strengthen transnational development - Irene Schöfberger (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
Intense negotiations about migration management policies are taking place inside the European Union (EU), and between the EU and African states. Although these two negotiation processes are often analysed separately, they are actually interlinked. Drawing on interviews with representatives of European and African states and regional organisations as well as on policy analysis, this Briefing Paper argues that negotia¬tions inside the EU restrict EU-Africa cooperation on migration in two ways: first, by transmitting a strengthened focus on border control from the internal to the external dimension of EU migration management policies; second, by framing migration in a narrow way, which has hindered progress with regard to transnational development. Intra-EU policy negotiations on migration are essential for the evolvement of EU-Africa cooperation on migration. Their increasing focus on border controls in Europe and Africa hinders the adoption of policies that support the potential of migration to contribute towards transnational resilience and development. Therefore, addressing the divisions on the internal dimension of EU migration management policy is a prerequisite for identifying sustainable EU-Africa cooperation pathways and supporting African migrants as actors of transnational development. There are two important lessons that the Commission and the member states can learn from their difficulties in reaching an internal agreement on how to manage migration inside and outside the EU. The first lesson is that they need to address the challenge of balancing European national and transnational competencies and approaches. This challenge is inherent to the EU being a transnational union of nation states. The second lesson is that they need to take into greater consideration the needs of vulnerable citizens of both European and African countries. In particular, the EU and its member states should: Focus on the internal dimension of migration management and rebalance the current distribution of national and EU transnational competencies on migration. This is needed to address the conflicts of competencies that are currently hindering the nego¬tiations on common policies. In particular, they should explore the feasibility of transferring some national competencies to the EU, including through the creation of a pilot EU Agency on Labour Migration. Introduce effective mechanisms of transnational responsibility-sharing in the EU in order to safeguard free movement within the Schengen Area. In particular, they should foresee an EU relocation system based on incentives and sanctions as part of a reform of the Dublin Regulation. Take the needs of young and low-skilled workers as well as migrant European workers into greater consideration by promoting employment, job security and labour rights, with funding through the European Social Fund. Reintroduce policy and development cooperation measures supporting the potential of African migration to contribute towards transnational resilience and development and provide adequate funding through the Multiannual Financial Framework 2021-2027. In particular, such measures should support self-determined strategies of African migrants, for example by facilitating circular mobility and the transfer of remittances.
Keywords: 330; Flucht und Migration; Regionale + globale + transnationale Governance